Engineering design process - Haik, Yousef , 1963-; Shahin, Tamer M. (Cengage Learning, 2011)
Deals with the essential components of the design process and uses case studies, labs, and group projects to show their application. This title helps students learn that the design process is a set of procedures that help them solve engineering problems